Single Turnover Reveals Oxygenated Intermediates in Toluene/o-Xylene Monooxygenase in the Presence of the Native Redox Partners - Liang, Alexandria Deliz (J Am Chem Soc, 2015)
Toluene/o-xylene monooxygenase (ToMO) is a non-heme diiron protein that activates O(2) for subsequent arene oxidation. ToMO utilizes four protein components, a catalytic hydroxylase (ToMOH), a regulatory protein (To-MOD), a Rieske protein (ToMOC), and a reductase (ToMOF). Here, we examine O(2) activation and substrate hydroxylation in the presence of all four-protein components. Studies of this system demonstrate the importance of ToMOC for formation of the active hydroxylating species that are not revealed when dithionite and mediators are used as the reductant. This reactivity is discussed in light of other O(2)-activating, non-heme diiron enzymes.